Homogeneous Catalysis of O-Silylation Reactions Using Tris (Acetylacetonato) Cobalt (III) - Hikmat S.Hilal (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Tris (acetylacetonato) cobalt (III), (Co(acac)3), has been used to catalyze o-silylation reactions of R 3 Siff (R.z.Et,Et0) with R OH (Rt-Et, i-Pr, t-.Bu and C6Hj-). No reaction has been observed at room temperature, but the reaction is apparently enhanced when carried out at a higher temperature. The rate of the reaction varies with varying the concentration of the saline or the alcohol. Using different types of alcohols and silanes greatly affects the rate of the reaction. The rate of the reaction is affected by varying the concentration of the complex (Co(acaci6)).